Generalized structured component analysis : a component-based approach to structural equation modeling - Hwang, Heungsun; Takane, Yoshio (Chapman & Hall/CRC Statistics in the Social and Behavioral Sciences., 2015)
Developed by the authors, generalized structured component analysis is an alternative to two longstanding approaches to structural equation modeling: covariance structure analysis and partial least squares path modeling. Generalized structured component analysis allows researchers to evaluate the adequacy of a model as a whole, compare a model to alternative specifications, and conduct complex analyses in a straightforward manner. Generalized Structured Component Analysis: A Component-Based Approach to Structural Equation Modeling provides a detailed account of this novel statistical methodolo.